Health-related quality of life in cancer patients treated with immune checkpoint inhibitors in randomised controlled trials: A systematic review and meta-analysis. (December 2021) - Boutros, Andrea; Bruzzone, Marco; Tanda, Enrica T.; Croce, Elena; Arecco, Luca; Cecchi, Federica; Pronzato, Paolo; Ceppi, Marcello; Lambertini, Matteo; Spagnolo, Francesco
Abstract: Background: Immune checkpoint inhibitors (ICIs) have revolutionised clinical practice in oncology in the last years, leading to a survival benefit in several tumour types. To investigate whether these benefits are associated with improved quality of life, we conducted a systematic review and meta-analysis comparing patient-reported outcomes (PROs) between ICIs and standard chemotherapy (CT) in patients with advanced solid tumours. Methods: Clinical trials comparing the efficacy of ICIs (either programmed death receptor-1 and programmed death-ligand 1 inhibitors or cytotoxic T-lymphocyte antigen 4 inhibitors, as single agent or in combination) versus CT were included. Trials evaluating treatment with ICIs plus CT versus CT alone were also included, whereas studies in which the control arm included other anticancer agents (such as targeted therapy and other ICIs) or placebo alone were excluded. The aim of our meta-analysis was to compare PROs in subjects treated with ICIs or ICIs plus CT (intervention) with those reported by patients receiving CT (control). The co-primary endpoints were time from baseline to first deterioration in PROs, defined as the time from baseline to the first clinically significant deterioration in PROs, and the changes in PROs from baseline to follow-up between ICI and CT treatment groups (PROSPERO registration number CRD42021247440). Results: A total of 8341 patients from 17 randomised trials of ICI versus CT were included in the analysis. Treatment with ICI delayed clinical deterioration over standard CT in Global Health Status/QoL EORTC QLQ-C30 (hazard ratio [HR] 0.81; 95% confidence interval [CI], 0.74–0.89), and in both EQ-5D utility index (HR 0.65; 95% CI, 0.52–0.82) and EQ-5D visual analogue scale (VAS; HR 0.70; 95% CI, 0.61–0.80). The difference in mean change between the ICI-treated group and the CT-treated group was 5.82 (95% CI, 4.11–7.53) in favour of ICI. Similarly, in the EQ-5D, the mean change differences favoured treatment with ICIs in both Utility Index and VAS, with differences of 0.05 (95% CI, 0.03–0.07) and 5.41 (95% CI, 3.39–7.43), respectively. Conclusions: ICIs are associated with higher levels of quality of life and longer time to clinical deterioration on several PROs scales compared with CT in different types of solid tumours. Highlights: First meta-analysis on health-related quality of life directly comparing ICIs and chemotherapy. A total of 8341 patients included from 17 trials of seven different tumour histology. ICIs linked to benefit in patient reported outcomes compared with standard chemotherapy.